STUDYING THE ESSENCE, TYPES AND GENRES OF FINE ART - Sharabaev Ulugbek Mukhamedovich (Bright Mind Publishing, 2025)
The visual arts encompass a variety of creative expressions that are concerned with aesthetic principles, emotions, and ideas. This article explores the essence of the visual arts and their importance in human culture and society. It explores the diverse types and genres within the visual arts, shedding light on the rich tapestry of artistic practice that has developed over the centuries.
Keywords: Visual arts, oldest and most revered, other media, paper or wood, drawing.